Indonesian Socio - Political Realities Reflected At Ayu Utami's Saman (1998): A Sociological Approach - Dewi, Riyana Kusuma; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2014)
This study is strived to reveal indonesian socio-political realities reflected in Ayu Utami's Saman (1998) novel. Saman (1998) is analyzed by using a sociological approach. The analysis is done by determining two objects: the first is describing social background of Indonesia in twentieth century and the second is analyzing the issue based on a sociological approach. This research is a descriptive qualitative research. There are two types of data sources. The primary data sources is Ayu Utami's Saman (1998) novel translated by Pamela Allen. The secondary data sources are books, journals, and internet sources related to the study. The two kinds of data collected through library research and analyzed with descriptive analysis. Based on the research, the researcher pulls the following conclusion. Based on a sociological approach, there is a close relationship between the novel and the realities of Indonesian life. The novel is as an object in which the author presents her world view corresponding with the socio - political life of New Order Era.